Jinlong capsule inhibits migration and invasion in human glioblastoma cells via the modulation of mTOR/S6 signaling pathway - Shi J; Zhang W; He L; Kong F; Pan M; Guo J; Xu X; Guo J; Wang H; Wang Y (Dove Medical Press, 2019)
Jingren Shi,1 Wenli Zhang,2 Lu He,2 Fanhong Kong,2 Meichen Pan,1 Jingjing Guo,1 Xinmin Xu,1 Jie Guo,1 Huizhu Wang,1 Yajie Wang11Department of Clinical Laboratory, Beijing Ditan Hospital, Capital Medical University, Beijing 100015, People’s Republic of China; 2Department of Clinical Laboratory, Beijing Tiantan Hospital, Capital Medical University, Beijing 100050, People’s Republic of ChinaAim: To investigate the anticancer effects of Jinlong capsule (JLC) against human glioblastoma cells and the possible underlying mechanism.Methods: Cell Counting Kit-8 and colony formation assay were adopted for the analysis of cell viability. Cell invasion and migration were evaluated by transwell and wound healing assays. Then, the expression level of mammalian target of rapamycin (mTOR), phosphorylated mTOR (p-mTOR), S6 and phosphorylated S6 (p-S6) were determined by western blotting.Results: The results showed that JLC significantly inhibited human glioblastoma cell proliferation, invasion and migration in a dose-dependent manner. The expressions of p-mTOR and p-S6 were dramatically suppressed by JLC. Furtherly, inhibition of mTOR reduced the cell migration and invasion, while the mTOR agonist (MHY1485) could partially reverse the anti-migration and anti-invasion activity of JLC.Conclusion: The above results suggested that JLC would be a potential candidate for the treatment of glioblastoma.Keywords: Jinlong capsule, invasion, migration, glioblastoma, mTOR, S6